JURIDICAL ANALYSIS OF CRIMINAL SANCTIONS AGAINST PERPETRATORS OF ATTEMPTED THEFT USING FIREARMS (A STUDY OF DECISION NUMBER 286/PID.B/2025/PN SRH) - Maruli Sihombing; Muhammad Hizbullah (Jurnal Ilmu Hukum dan Keadilan, 2026)
Based on the research results, it shows that the legal provisions for the crime of attempted theft using firearms are regulated in Articles 362, 363, 364, 365 of the Criminal Code, Article 53 of the Criminal Code, and Article 1 Paragraph (1) of Emergency Law Number 12 of 1951 concerning the Misuse of Sharp Weapons, Firearms and Explosives. The judge's consideration in deciding the case of the crime of attempted theft using firearms in Decision Number 286/Pid.B/2025/PN Srh is appropriate because it has considered the facts and evidence presented and connected them with the existing evidence. The legal analysis of the punishment for the perpetrator of attempted theft using firearms in the Decision of the Sei Rampah District Court Number 286/Pid.B/2025/PN Srh is inappropriate because it only sentenced the defendant to 9 years in prison. The crime of attempted theft with violence and possession and use of firearms without a permit should be sentenced to 12 years in prison.